2019
DOI: 10.3390/inorganics7020014
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Pathways of Waters and Protons in Photosystem II and Cytochrome c Oxidase

Abstract: Photosystem II (PSII) uses water as the terminal electron donor, producing oxygen in the Mn4CaO5 oxygen evolving complex (OEC), while cytochrome c oxidase (CcO) reduces O2 to water in its heme–Cu binuclear center (BNC). Each protein is oriented in the membrane to add to the proton gradient. The OEC, which releases protons, is located near the P-side (positive, at low-pH) of the membrane. In contrast, the BNC is in the middle of CcO, so the protons needed for O2 reduction must be transferred from the N-side (ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 157 publications
(265 reference statements)
3
18
0
Order By: Relevance
“…Experiments show chloride depletion blocks the advancement of S-state transition beyond S 2 ( Ono et al, 1986 ; Pokhrel and Brudvig, 2014 ). Simulations show depletion of chloride leads to formation of a salt bridge between D1-Asp 61 and D2-Lys 317 hindering proton loss ( Rivalta et al, 2011 ; Amin et al, 2016 ; Kaur et al, 2019 ).…”
Section: Photosystem IImentioning
confidence: 99%
“…Experiments show chloride depletion blocks the advancement of S-state transition beyond S 2 ( Ono et al, 1986 ; Pokhrel and Brudvig, 2014 ). Simulations show depletion of chloride leads to formation of a salt bridge between D1-Asp 61 and D2-Lys 317 hindering proton loss ( Rivalta et al, 2011 ; Amin et al, 2016 ; Kaur et al, 2019 ).…”
Section: Photosystem IImentioning
confidence: 99%
“…Control by temperature that the channels make a close and open form by the amino acid to influence the water-protein interactions in the channel. The channel water diffusion may make a key role in controlling the respiration reaction for the proton coupled electron transfer 26,[47][48][49] and the O 2 reduction. It has been found that the protons released need requires a proton-transferring pathway (a "proton well") in the relevant protein.…”
Section: Features Of Tetramer Pfk-1s With Interior Site Connection Wamentioning
confidence: 99%
“…Pumps have proton loading sites (PLS), a residue or group of residues whose proton affinity changes dramatically through the reaction cycle, so a proton is loaded, held and then released through the reaction cycle. A requirement for a pump to function is that the PLS proton affinity must change so that its effective pK a shifts substantially, from several pH units above the pH for proton loading to several pH units below the pH for proton unloading [6,7]. Smaller changes in affinity or those where the change of effective pK a s in different states that do not cross the pH of the surroundings will not cause the PLS to alter protonation state.…”
Section: Introductionmentioning
confidence: 99%
“…In CcO the energy required is provided by the reduction of oxygen at the Binuclear center (BNC) located in the center of the protein. The BNC consists of a heme group and a copper site and a covalently-linked Tyr residue [7,9,10]. In the overall redox reaction cycle CcO reduces one oxygen molecule to water, driving a reaction cycle that results in uptake of 4 protons from the N-side for chemistry and additional protons pumped from N-to P-side [7,9]: ,…”
Section: Introductionmentioning
confidence: 99%